RESOLUSI KONFLIK LAHAN ANTARA PT.CITRA SUMBER SEJAHTERA DENGAN DESA PAUHRANAP DAN DESA PESAJIAN - Herwina Oktafiani; Harapan Tua RFS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Land is a basic human need, not only having high economic value, but also philosophical, political, social and cultural values. It is not surprising that land becomes a special property that constantly triggers various complex and complicated social problems. One of the agrarian conflicts that occurred in Indragiri Hulu Regency was the conflict between PT Citra Sumber Sejahtera and Pauhranap and Pesajian villages. This longstanding conflict is because the community feels that the company has not compensated the land they own. This study aims to find conflict resolution due to the conflicts that occur. The theory put forward by Fisher in Tisa (2017) is Negotiation, Mediation, and Arbitration. This study uses the method of observation, documentation, data analysis and interviews. Secondary data obtained from village offices, relevant government agencies, BPS, books, journals, or data from the internet containing related theories or research results. The results of this study explain that the conflict in the villages of Pauhranap and Pesajian and PT. The image of Sumber Sejahtera is destructive, accompanied by acts of violence and destruction of facilities. However, the conflicts that have occurred so far have been successfully quelled by the officials of the two villages and the company by conducting mediation by paying compensation. Keywords: Resolution,Conflict, Land Conflict